A Checklist of the Land and Freshwater Mollusks of Virginia - Dorothy E. Beetle (Hello World!, 1973)
Previous molluscan checklists of Virginia material have been limited to certain counties and have been based on material in private collections. The following checklist attempts to bring together all published county records and locality records from the collections of the United States National Museum, the Museum of Comparative Zoology at Harvard, the American Museum of Natural History, the Museum of Zoology of the Ohio State University, and material in private collections.